If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(2w + 1) + -9 = 0 Reorder the terms: 5(1 + 2w) + -9 = 0 (1 * 5 + 2w * 5) + -9 = 0 (5 + 10w) + -9 = 0 Reorder the terms: 5 + -9 + 10w = 0 Combine like terms: 5 + -9 = -4 -4 + 10w = 0 Solving -4 + 10w = 0 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 10w = 0 + 4 Combine like terms: -4 + 4 = 0 0 + 10w = 0 + 4 10w = 0 + 4 Combine like terms: 0 + 4 = 4 10w = 4 Divide each side by '10'. w = 0.4 Simplifying w = 0.4
| -5(y-6)+2(3y-4)=-10 | | 9x+102=0 | | (R-3)/3=5 | | 2+21=x+10 | | -101/3(93) | | -4x+10(3-4x)=11x+6(5+2x) | | 4+(k+5)=13 | | -4(x+2)+6x= | | 3(d+2)=-3d-12 | | -42=-6/7w | | 9-h-15=93 | | 25+m=-6 | | 3+5p=95 | | -(v+5)+5(2v-6)= | | -2(x-1)=8x+32 | | 3x+8=10x-3 | | 3(2t-4)+2t=24+t | | D+-1=-19 | | 9y+3+4y=-23 | | -8=5u+7 | | f^-1(4)=3x-4/5 | | X=7y+6 | | X=7y+y | | sin=0.8191 | | -2(y+5)+2y= | | 2x-4=-1(5x-3) | | -1(1-5x)= | | x^2-48x+9=0 | | 135=9(f-897) | | (2w-2)(w)=65 | | 4(v-4)-6v= | | 23(m+27)=644 |